Four Domain Model of Environmental Adaptability for HX Serial Locomotive - ZHANG Kaihui (机车电传动)
The study on environmental adaptability of HX serial locomotives is an important means of improving the quality and market competition. Aiming at the disadvantage of single and scattered means of locomotive working condition test and evaluation in the past, a new integrated evaluation method of the four-domain physical quantities, i.e. mechanical, electrical, thermal and wet was constructed, and the environmental adaptability of traction converter, the key component of HX locomotive in Lanxin line was evaluated. The measured data showed that the values of the measured points in the mechanical, electrical, thermal and wet fields were within the prescribed design values, and the temperature and vibration had a greater impact on the key components. Finally, suggestions for further optimization of cooling system and vibration reduction scheme in converter cabinet were put forward.